Medicinal Plant Inventory in Pasie Jambu Village, Kaway XVI Subdistrict, West Aceh Regency - Syam, Nasrianti; Fadillah, Mardi; Rahma, Cukri (Universitas Labuhanbatu, 2024)
Indonesia has one of the greatest quantities of biodiversity in the world, which is utilized by industries such as medicines as a source of raw materials. As is the case with the inhabitants of Pasie Jambu Village, Kaway XVI Subdistrict, West Aceh Regency, medicinal plants contain substances that can be used to treat diseases of the human body or organs. The research aims to determine which plant parts are utilized by village communities, as well as the manner in which those parts are processed. Precisely on purpose, the snowball method was implemented. The findings derived from the interviews indicated that the inhabitants of Pasie Jambu Village utilized a total of 34 different plants. At 62%, the leaves are the most widely utilized part of the plant; at 3%, the roots, skin, and tubers are the least utilized. These plants are subjected to various processing methods, including boiling, pounding, smearing, and wiping. Among these, pounding is frequently employed at a rate of 52%, while chewing accounts for at least 3%